Effect of emimBF4 ionic liquid concentration on ionic liquid-polymeric membrane (ILPM) for CO2/CH4 separation - Mustafa, M.Z. (Institute of Physics Publishing, 2020)
In the current study, polyethersulfone based (emim)bf4 ionic liquid polymeric membranes (ILPMs) were synthesised for CO2 separation from CH4. Two weight percentages (10% and 20%) of (emim)bf4 ionic liquid was added in the prepared doped solution; flat sheet dense membranes were synthesised by the dry phase inversion method. Field Emission Scanning Electron Microscope (FESEM) was used to analyse membranes morphology. Elemental composition of the membranes was examined using Energy Dispersive X-ray (EDX). Distribution of IL in the polymer matrix was observed with the help of mapping. The gas permeation experiments were performed at ambient room temperature and 4 bar pressure. All membranes showed dense and non-porous structure which depicted the good compatibility of polymer and ionic liquid. Presence of additional elements such as nitrogen and fluorine in PES/emim bf4 membranes confirmed the presence of ionic liquid in the polymer. Mapping of fluorine element shown the uniform distribution of ionic liquid in the synthesised ILPMs. Membrane having ionic liquid 20 weight % showed a nearly 39-fold increase in CO2 gas permeability compared to pure polyethersulfone membrane and 2.31-fold increase in ideal selectivity of CO2/CH4. The synthesised ILPMs have immense potential for CO2 separation from natural gas. Â© Published under licence by IOP Publishing Ltd.